Handbook of research on fuzzy and rough set theory in organizational decision making - Sangaiah, Arun Kumar; Gao, Xiao-Zhi; Abraham, Ajith 1968- (Advances in Business Strategy and Competitive Advantage (ABSCA) Book Series, 2017)
"This book presents both empirical and applied research in the field of fuzzy set theory, and bridges the gap between the application of soft computational approaches and the organizational decision making process"--